Production of Mini Tuber Potato (Solanum tuberosum L.) PPT4 Zebra with Aeroponic System Through The Addition of Lighting Color Settings and Lighting Length - Maya, Dista Yufiana Aris; Ishartati, Erny; Nursandi, Fatimah; Rasyid, Harun; Husein, Syarief (Journal of Tropical Crop Science and Technology, 2024)
Potatoes (Solanum tuberosum L.) are carbohydrate-rich crops. Low potato productivity in Indonesia stems from farmers' inadequate access to quality seed potatoes. One solution to this issue is enhancing quality seed potato production, achievable through aeroponic systems. Lighting, whether incandescent or LED, can optimize potato mini tuber propagation in aeroponic systems. Research on lighting's effects on potato growth remains incomplete. This study aims to investigate how lighting color and duration affect mini tuber production of Solanum tuberosum L. PPT4 Zebra using aeroponic systems. Conducted in Jurangkuali, Bumiaji sub-district, Batu, the study employed a split plot design. The main plot consisted of lighting colors (WC): light yellow (WK), white (WP), and purple (WU). Subplots were lighting duration (LP) at 3 hours (LP 3) and 5 hours (LP 5), each replicated four times. Each replication comprised 8 samples, with 18 potato plant cuttings per population. Variables included plant height, stem diameter, leaf count, chlorophyll level, root length, tuber count, tuber diameter, budding seed count, and tuber weight. Data were analyzed using F-tests followed by BNJ tests at a 5% significance level. Results indicated no interaction between lighting color and duration. Purple lighting yielded the highest tuber count and weight, while 3-hour lighting duration yielded superior plant height, stem diameter, leaf count, and root length.